2022
DOI: 10.3390/nano13010026
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Behaviour of Metal-Oxide Nanomaterials in Various Biological Media

Abstract: Toxicological effects of metal-oxide-engineered nanomaterials (ENMs) are closely related to their distinct physical–chemical properties, especially solubility and surface reactivity. The present study used five metal-oxide ENMs (ZnO, MnO2, CeO2, Al2O3, and Fe2O3) to investigate how various biologically relevant media influenced dissolution behaviour. In both water and cell culture medium (DMEM), the metal-oxide ENMs were more soluble than their bulk analogues, with the exception that bulk-MnO2 was slightly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…Similar analyte loss during control experiments was reported by Avramescu et al, 2023 [32] at a lower AlCl 3 concentration of 1 mg/L. Considering the observed analyte loss, the authors suggested that the solubility reported may be considered an 'apparent solubility', which represents the portion of released Al that is not matrix bound [32]. Furthermore, particle formation has been noted by others when conducting in vitro exposures using AlCl 3 as well as within simulated intestinal fluid [38,39].…”
Section: The Impact Of Solubility On the Toxicity Of Monpssupporting
confidence: 82%
See 3 more Smart Citations
“…Similar analyte loss during control experiments was reported by Avramescu et al, 2023 [32] at a lower AlCl 3 concentration of 1 mg/L. Considering the observed analyte loss, the authors suggested that the solubility reported may be considered an 'apparent solubility', which represents the portion of released Al that is not matrix bound [32]. Furthermore, particle formation has been noted by others when conducting in vitro exposures using AlCl 3 as well as within simulated intestinal fluid [38,39].…”
Section: The Impact Of Solubility On the Toxicity Of Monpssupporting
confidence: 82%
“…Dissolution testing for all relevant MONPs and MOMPs was carried out by Avramescu et al, 2020 [ 31 ] and Avramescu et al, 2023 [ 32 ], the results of which were used to inform the toxicity testing conducted in the present study ( Table S1 ). MONPs were grouped as negligible (<1% dissolved), low (1–10% dissolved), moderate (10–70% dissolved), or highly soluble (>70% dissolved) according to Avramescu et al, 2023 [ 32 ], which was based on criteria reported in ENV/JM/MONO (2015) [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although zinc oxide (ZnO)‐coated urea has been tested as a Zn fertilizer (Milani et al., 2015), neither copper oxide (CuO) nor nickel oxide (NiO) has been used before as a coating material and none of the metal oxides have been tested to inhibit urea hydrolysis. These oxides are usually produced in the <100 μm particle size range and are highly insoluble in water, which might provide an added effect when used as a binder of delaying the dissolution of the urea core in addition to inhibiting urea hydrolysis (Avramescu et al., 2023; Irfan et al., 2018).…”
Section: Introductionmentioning
confidence: 99%